The Role of Compensation and Work Environment in influencing Employee Performance at PT. Welling Tapioca Jaya with Work Motivation as Intervening Variable - Rusmewahni, Rusmewahni; Gunawan, Hary (Universitas Efarina, 2021)
The purpose of this study was to examine the effect of (1) feelings on employee performance (2) work environment on employee performance (3) feelings on work motivation (4) work environment on work motivation (5) work motivation on employee performance (6) feelings on employee performance through work motivation as an intervention variable (7) work environment on employee performance through work motivation as an intervention variable. This study uses a quantitative research approach. The population in this study were all employees of PT Welling Tapioka Jaya, totaling 47 employees. The sampling technique uses saturated sampling technique which makes all members of the population as research samples. Methods of data collection using a questionnaire. Analysis tools: instrument test, classical assumption test, multiple linear regression analysis, t test and path analysis using SPSS version 25. The results of this study indicate that the environment and work environment partially affect employee performance and also work motivation. work motivation affects employee performance and based on the results of path analysis, it is found that work motivation cannot mediate the effect on employee performance and the work environment on employee performance